Low temperature stacking fault nucleation and expansion from stress concentrators in 4H-SiC. (15th October 2017) - Orlov, Valery I.; Regula, Gabrielle; Yakimov, Eugene B.
Abstract: Despite of intensive studies during the last two decades of nucleation and expansion of Shockley-type single or adjacent stacking faults (double stacking faults) in 4H-SiC, the involved mechanisms are far from being deeply understood. Thus, in this paper, the temperature and carrier injection dependence of nucleation and expansion of these defects from local stress concentrators have been investigated by cathodoluminescence and low energy electron beam irradiation. Their corresponding behavior depends on their multiplicity. Upon annealing, the single stacking faults are found to be nucleated at lower temperature than the double stacking faults and their mobility is lower. Under electron injection at room temperature, only single stacking faults are nucleated. The involved partial dislocations dragging the stacking faults are assumed to have different nature cores. Graphical abstract: Image 1